Carbohydrates and ginsenosides in shenmai injection jointly improve hematopoietic function during chemotherapy-induced myelosuppression in mice - Shiyu Zhang; Yinxiao Mi; Tingting Ye; Xiaoyan Lu; Li Liu; Jing Qian; Xiaohui Fan (Chinese Medicine, 2022)
Highlights Shenmai injection attenuates 5-FU-induced myelotoxicity in tumor-bearing mice. Both carbohydrates and ginsenosides in Shenmai injection promote hematopoiesis. Carbohydrates may regulate Glutathione metabolism and B cell receptor pathway.